Attitudes of prehospital emergency care professionals toward refusal of treatment: A regional survey in Turkey - Erbay, Hasan (Nursing ethics, 2014)
Introduction:Prehospital emergency medicine is a specific field of emergency medicine. The basic approach of prehospital emergency medicine is to provide patients with medical intervention at the scene of the incident. This special environment causes health professionals to encounter various problems. One of the most important problems in this field is ethics, in particular questions involving refusal of treatment and the processes associated with it.Objective:The objective of this study is to identify emergency health professionals’ views regarding refusal of treatment.Methods:This study was conducted with 356 health professionals who were on active duty in prehospital emergency health services. The data were collected through a form which included 10 statements. The participants were asked to indicate their level of agreement with the statements given by rating them between 0 and 10.Ethical considerations:Before conducting the research, permission was received from the local ethics committee. Participants were given written information about the purpose of the study. Participants were assured that their participation was voluntary.Results:The healthcare professionals with fewer years of experience in the profession and female participants adopted an attitude of giving priority to providing care. Young participants, in general, respected patient autonomy. However, paradoxically, when it comes to emergency medical cases, they expressed an opinion closer to paternalism.Conclusions:This study has found that prehospital emergency health professionals generally respect the patient’s right to refuse treatment; however, they do not prioritize this right when there is a life-threatening situation or when the person does not have decision-making capacity. In these cases, prehospital emergency health professionals tended to adopt a more paternalistic approach.